KRISIS METAFISIKA DAN FILSAFAT SEBAGAI TUGAS BERPIKIR: PERSPEKTIF HEIDEGGER (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2023)
This article aims to reflect further Heidegger's thought on the crisis of metaphysics and philosophy as a task of thinking. Philosophy since ancient times, even today, has been oriented to seek and formulate the essential and universal concept. Is it true that searching for the ontotheological nature is the most important task of philosophy? Is it true that these single principles can reflect the truth? By using the method of library researh and critical analysis of Heidegger's works and studies on the crisis of metaphysics, this article shows that philosophy essentially does not aim to formulate absolute, universal and single notion. Philosophy is also not a project of producing standard, abstract, sophisticated and technical concepts. The important task of philosophy is to encourage men to think, an art of understanding. Thinking is not a calculative thinking (instrumental-technical rationality) but meditative and reflective thinking. Under philosophy as the task of thinking, Being, namely the totality of reality, is responded with amazement, humility and simplicity. Philosophy must liberate itself from the metaphysical trap of totalitarian power which tends to hegemonize others in the name of a single truth, to philosophy that celebrates the plurality of truths with humility dan simplicity. That is the real meaning of philosophy as philo-sophia, the love of wisdom.